Answer:
I think the answer is undefined because the question above is an expression of f of x not a statement of variation which should have a constant of proportionality
Answer:
<h2>(g ∘ h)(x) = x² - 6x + 9</h2>
Step-by-step explanation:
g(x) = x²
h(x) = x - 3
To find (g ∘ h)(x) substitute h(x) into g(x) that's for every x in g(x) replace it with h(x)
That's
(g ∘ h)(x) = ( x - 3)²
= x² - 3x - 3x + 9
We have the final answer as
<h3>(g ∘ h)(x) = x² - 6x + 9</h3>
Hope this helps you
Sharon would spend $2.50 for the light bulbs she wants.
y = 7
x = 4 is a vertical line parallel to the y- axis passing through all points with an x- coordinate of 4
A line perpendicular to x = 4 will be a horizontal line parallel to the x- axis with equation y = c where c is the value of the y- coordinate the line passes through.
line passes through (5 , 7) with y- coordinate 7
The equation is therefore y = 7